ER biogenesis without stress: how the ribosome receptor, p180, defines a developmental program beyond the UPR - Benyamini, Payam; Meyer, David I. (Frontiers in Cell and Developmental Biology, 2025)
The endoplasmic reticulum (ER) plays a central role in protein and lipid biosynthesis, quality control, and secretion. While its functional roles are well characterized, the mechanisms underlying ER biogenesis remain less defined. Developmental transitions in secretory tissues such as liver, pancreas, mammary gland, and plasma cells illustrate the remarkable capacity to expand their ER network in response to physiological demand. Central to this process is the ribosome receptor p180, a vertebrate-specific integral ER membrane protein whose expression is both necessary and sufficient for rough ER proliferation. Studies in yeast first demonstrated that overexpression of membrane proteins, including HMG-CoA reductase and domains of p180, induces membrane proliferation, thereby establishing yeast as a tractable model for ER biogenesis. In mammalian systems, p180 uniquely links membrane protein expression with biosynthetic scaling, enhancing ribosome binding, mRNA stabilization, lipid biosynthesis, and Golgi biogenesis. Gain- and loss-of-function approaches in human monocytic THP-1 cells confirm that p180 is indispensable for establishing a high-capacity secretory cells phenotype, coordinating the transition from sparse to abundant rough ER and secretory output. Importantly, p180-driven ER proliferation occurs independently of the unfolded protein response (UPR), highlighting distinct yet complementary mechanisms of ER remodeling: p180 as a constitutive biosynthetic scaffold and the UPR as a stress-induced regulator. Together, these findings position p180 as a master determinant of secretory architecture, with implications for development, immunity, and disease. Understanding the molecular underpinnings of p180 function and its integration with lipid metabolism and translation control will advance both basic cell biology and therapeutic strategies targeting secretory dysfunction. Recent work also suggests that p180-mediated ER expansion is dynamically tuned to nutrient availability and growth factor signaling, further linking organelle biogenesis to cellular metabolism. Dysregulation of p180 expression or function may contribute to a variety of pathological states such as cancer, neuronal dysregulation, and atherosclerosis where ER homeostasis is disrupted. Due to its vertebrate-specific origin, p180 also represents an evolutionary concerved lineage that enabled the diversification of complex secretory systems. Ultimately, dissecting the molecular circuits that govern p180 function promises to refine our understanding of organelle plasticity and to identify novel targets for therapeutic intervention.